Ela tem peito, a outra tem peito; sou des-peitada, muito prazer: análise compreensiva com mulheres mastectomizadas - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The experience of receiving the communication of the breast cancer diagnosis for a woman establishes a crisis where her vulnerabilities will be exposed, with the loss of the femaleness. Contract breast cancer is equivalent to be close to death, and this feeling brings together the sensation of sadness and despair. The mastectomy surgery brings a mutilation; and the chemotherapy and radiotherapy, brings depression over the loss of hair, eyelashes and body hair. The problems related with the breast cancer are felt not only by the patients, but also by all the people living in their social environment. Some people tend to help these women, others tend to simply abandon them. A routine of separation, loss, frustration and changes takes place; and from where you least expect, comes a valuable help, the Grupo de Apoio às Mulheres Mastectomizadas da Amazônia GAMMA (Support Group for mastectomized women of the Amazon). From the living experience in this group, the present qualitative research, developed according to the precepts of the phenomenological method, which advocates the understanding of the other through his own speech. The research collaborators were ten women mastectomized for at least one year who attended the GAMMA at the Fundação CECON (CECON Foundation), in Manaus, Brazil. The study was conducted through audio-recorded interviews and based on the request that participants describe how did they experienced the moment of diagnosis, surgery and GAMMA group entry, as well as what they think about everything that related with the issue. From the speeches were recognized the Meaningful Units that originated Analysis Categories and served to understand the existentialism of these women before the diagnosis of breast cancer, enabling comprehensive synthesis of the phenomenon "being-in-the-world-with-breast-cancer". The study revealed that the experience of diagnosis of breast cancer is meant as a time of great impact and generates profound changes in various aspects of life: family, personal and social. Faith, the reflections, the possibility of learning, family support and the GAMMA group support emerge as coping factors. Permeating these aspects, the experience of time in its tripartite temporal nexus where past, present and future are experienced simultaneously and guilt for the possibility of a disease that could had been prevented, concluded that "being-in-the-world-with-breast-cancer" is a painful and impacting experience, full of radical changes, but with possibilities for learning, fighting, healing and overcoming.
Keywords: Câncer de Mama; Diagnóstico; Mastectomia; Fenomenologia; Superação; Breast Cancer; Diagnosis; Mastectomy; Phenomenology; Overcoming; CIÊNCIAS HUMANAS: PSICOLOGIA